REFORMING OF UKRAINIAN ECONOMY: THE URGENCY AND THE PRIORITIES - Savelyev, Yevhen; Kurylyak, Vitalina (Journal of European Economy, 2017)
Approaches to economic reforms in Ukraine since independence are considered. It is shown that they were half and created the conditions for oligarchic economy. Two trends which were of pro-Western or pro Russian orientation had dominated in the reformist movement. The idea of systematic changes in the economy, which also must cover all political, legal, social and economic institutions, pre-reform of which should be a court reform is developing. Qualities that should be inherent by reformers are forming. Reforms should bring down oligarchic system and provide change in the direction of the country of export orientation from the Russian market to the Europe, Asia and America one. The idea according to which the center of reform initiatives should be a system of Education, which should encourage the inclusion of Ukraine in scientific leadership especially in the military-industrial complex, the achievement of which are able to create a chain reaction effect and spread to other industries is substantiated.